The Effect of Price, Customer Satisfaction, and Excellent Service on Consumer Loyalty: A Study at biMBA AIUEO - Achmad, Listian Indriyani; Kustiawan, Chairunnisa Abdini Amalia; Saptono, Edy (DPPM Universitas Pelita Bangsa, 2023)
The purpose of this study is to determine the effect of price, customer satisfaction, and service excellence on consumer loyalty at biMBA AIUEO in South Tambun. This research method used was a quantitative approach with Multiple Linear Regression. The population for this study were consumers/parents of biMBA AIUEO students. Samples were taken using a simple random sampling technique. The sample amounted to 100 people. The results showed the influence of price, customer satisfaction, and excellent service on consumer loyalty at biMBA AIUEO Tambun Selatan. This study resulted in the following conclusions: 1) The price offered by biMBA AIUEO has a positive and insignificant influence on consumer loyalty at biMBA AIUEO. 2) The study found that customer satisfaction at biMBA AIUEO has a significant effect on consumer loyalty. This would infer that biMBA AIUEO provides services that are in accordance with consumer expectations. 3) The study also found that the excellent service provided by biMBA AIUEO has a significant positive effect on consumer loyalty.